A suscetibilidade in vivo ao benzonidazol das Unidades Discretas de Tipagem (DTUs) de Trypanosoma cruzi: uma revisão sistemática - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Chagas disease (CD), discovered in 1909 by Carlos Chagas, is caused by Trypanosoma cruzi, a heteroxenic parasite, which has a complex biological cycle, different evolutionary forms throughout its development process and high heterogeneity. Its vector is hematophagous insects, popularly known as “kissing bugs”. There is no vaccine for CD and, in Brazil, only one drug is indicated for the treatment: benznidazole. Many studies point to discrepancies in the parasite's response to benznidazole, and some suggest that the genetic variability of T. cruzi may be directly related to the parasite's susceptibility to treatment with benznidazole (Bz). The aim of this systematic review was to gather evidence on DTUs (nomenclature used to categorize molecular strains of T. cruzi) and in vivo susceptibility to benznidazole. The articles were selected through the CAPES Periódicos portal, which includes several databases, including: Web of Science, Scopus, Lilacs, Pubmed and SciELo. Specific descriptors were used, such as “strains”, “Trypanosoma cruzi”, “in vivo”, “benznidazole”, among others. Initially, 407 articles were located, after the primary screening with application of relevance test 1, 28 articles remained that were submitted to the second relevance test, leaving 9 articles, which were included in this work. As a result, it was concluded that it cannot be stated that the susceptibility profiles of T. cruzi to treatment with benznidazole are only, or directly related to their respective DTUs. Furthermore, although the division into DTUs is very valid, there is a lack of studies that corroborate the establishment of a classification pattern that does justice to the behavioral diversity of the different strains of T. cruzi. New genetic and ecoepidemiological studies are needed for this approach to succeed.
Keywords: DTU; Trypanosoma cruzi; doença de Chagas; suscetibilidade; benzonidazol; DTU; Trypanosoma cruzi; Chagas disease; susceptibility; benznidazole; CNPQ::CIENCIAS BIOLOGICAS